PHRASEOLOGISMS IN THE RUSSIAN LANGUAGE - Safarova Zulfiya Karimovna; Khudaynazarova Aziza Valievna (Galaxy International Interdisciplinary Research Journal, 2024)
This scientific article delves into the complex world of phraseological units in the Russian language, studying their cultural meaning, linguistic structure and forms of use. Phraseologisms, or expressions that do not have a literal meaning, play a crucial role in communication, reflecting the unique cultural heritage and historical evolution of the language. In this article, we analyze the features of Russian phraseology, its origin, semantic complexity and impact on the understanding and expression of the language.